In-hospital outcomes and costs of surgical stabilization versus nonoperative management of severe rib fractures. Issue 4 (October 2015) - Majercik, Sarah; Wilson, Emily; Gardner, Scott; Granger, Steven; VanBoerum, Don H.; White, Thomas W.
<x xml:space="preserve">Abstract</x> BACKGROUND One factor that has precluded the wide adoption of surgical stabilization of rib fractures (SSRF) is the perception that it is too expensive to surgically repair an injury that will eventually heal without intervention. The purpose of this study was to compare in-hospital outcomes, costs, and charges for SSRF patients with a series of propensity-matched, nonoperatively managed rib fracture (NON-OP) patients at a single Level 1 trauma center. METHODS All patients admitted with rib fractures between January 2009 and June 2013 were identified. Patient demographics, injury, cost, and charge data were collected. Two-to-one propensity score matching was used to identify NON-OP patients who were similar to the SSRF patients. Zero-inflated negative binomial regression was conducted to assess the relationship among SSRF, intensive care unit (ICU) length of stay (LOS), and ventilator days. Cost and charge information was compared using Wilcoxon rank-sum tests. RESULTS A total of 411 patients (137 SSRF, 274 NON-OP) were included in the analysis. Ventilator days and ICU LOS in days were not different between the SSRF and NON-OP groups when compared using the Wilcoxon rank-sum test. Ventilator and ICU days were less for SSRF by 2.24 days and 1.62 days, respectively, using zero-inflated negative binomial analysis to exclude the large number of patients who had 0 day on the ventilator and/or in the ICU. SSRF patients had higher hospital costs and total relevant charges compared with the NON-OP patients. Subgroup analysis of patients requiring mechanical ventilation who did not have head injury showed decreased ventilator days (median, 3 days vs. 5 days; p = 0.03) and need for tracheostomy (5% vs. 23%, p = 0.02) in SSRF versus NON-OP, respectively. In this subgroup, there was no difference in hospital costs and charges between SSRF and NON-OP. CONCLUSION SSRF patients have shorter ICU LOS and less ventilator days than NON-OP across a diverse group of patients. Hospital costs and charges for SSRF patients are higher. In mechanically ventilated patients who do not have head injury, in-hospital outcomes are better, and there is no difference in hospital costs and charges. Further prospective cost-effectiveness research will determine whether improved quality of life and ability to return to meaningful activity sooner outweighs the increased costs of the acute care episode for SSRF patients. LEVEL OF EVIDENCE Epidemiologic study, level III.